Raison d'état, Religion, and the Body in The Rape of Lucrece - Mohamed, Feisal G. (Religions, 2019)
With an emphasis on the religious figuration of its heroine's chaste body, the present essay explores the political dynamics of The Rape of Lucrece. The poem draws on Roman religion and Christianity: Lucrece is an emblem of purity, with echoes of the flaminica or Vestal virgins, and her spotlessness anticipates Christ's. Seeing these qualities allows us to engage the poem's gender dynamics and its politics, with both of these being centered on issues of property. While The Rape of Lucrece has been enlisted as an artifact of late Elizabethan republican culture, its depiction of the expulsion of the Tarquins need not lead us to that conclusion. It is nonetheless a product of the political anxieties of Elizabeth's final years.